Drought management in the urban water supply system of Canal de Isabel II [Part 2. Examples of application] - Cubillo F.; Ibáñez J.C. (Drought management guidelines technical annex, 2007)
The main objective of the Supply manual developed by Canal de Isabel II (Spain) is to establish the general planning and operation guidelines of the supply system, to ensure water supply to urban centers in compliance with all established standards. The supply manual expresses the protocols and good practices to: (i) Establish the risks of scarcity and incapacity of the supply system to satisfy all demands. (ii) Establish efficient management policies of the resource and water demand. (iii) Ensure an integrated and sustainable management of resources. (iv) Establish guidelines to operate the supply system handling short-term outlook. (v) Integrate the satisfaction of environmental constraints and sustainability of related ecosystems into the operation of the supply system. (vi) Manage the supply under conditions of drought and scarcity of resources. (vii) Manage the supply system in case of large-scale contingencies and anomalies, such as floods. (viii) Plan actions to guarantee the water supply in the medium and long term with the established risk level.